A comparative analysis of coupled-inductors designs for the Y-Source DC-DC converter - Neto, Carlos Miguel Büchele [UNESP]; Santos, Rafael [UNESP]; Gonçalves, Flávio Alessandro Serrão [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this paper, a comparative analysis of different coupled-inductor designs applied to Y-Source DC-DC converters is presented. Many works in the literature discuss the impedance source networks but few analyze the implications of the coupled-inductor design on the converter operation, considering the impact of equivalent series resistances or core losses. Hence, this paper aims to evaluate the impact of three different coupled-inductor designs on the Y-Source DC-DC converter efficiency and core temperature, considering the strategy of equivalent series reduction by Litz wires with different wires number or core stacking, to reduce core reluctance. Using a DC-DC Y-Source converter with 230 W rated power, the different design strategies are outlined such that the operational requirements are met. Through simulation and experimental results, it can be observed that the adoption of a greater number of wires in the Litz arrangement is more effective to increase efficiency when compared to core stacking. However, lower temperatures are achieved only with the core stack, and leakage inductance issues arise due to loose windings with a reduction of effective voltage gain. The results of this work help to understand the relevance of different designs of coupled inductors and how they reflect on the efficiency of the converter and the core temperature. Furthermore, it can be used to improve the design of Y-source converters and advance the technological status of this power converter topology.
Keywords: Coupled-inductor; Impedance Source Network; Power and Energy Systems; Power Electronics; Renewable Energy; Y-Source